"Developing auditors ’tasks in raising the efficiency of environmental auditing to rationalize environmental costs "From the point of view of auditors and university academics - Ghazali, Mohammed Hazem Ismail (Journal of Economic, Administrative and Legal Sciences, 2018)
The development of the is one of the most important steps required by environmental costs, which is through environmental auditing, environmental auditing, looking for gaps in the calculation of these costs, and reducing the environmental cost is one of the most obstacles facing auditors’ tasks for environmental auditing. It is necessary to resolve these obstacles, which should be the beginning of the detection of errors faced by the auditor in the performance of his functions and those processes to be developed is the diagnosis of environmental pollution in the industrial units The aim of those operations is to develop the functions of the auditor, For environmental auditing in the treatment of failures that do not care to calculate the environmental costs and identify the wastes that affect the continuity of the company in the long run as a result of environmental damage and turn Governments are closing those companies violating the problem of research in the lack of integration between the determination of the auditor’s responsibilities to determine the role In the audit of environmental accounting and the search for the causes of these pollutants with increased control effective, and the audit has not been integrated and has not settled in the application yet in addition there are differences in the application process without taking into account the importance of auditing accounting Environmental auditors by giving an opinion on the veracity and fairness of the presentation of financial statements on environmental aspects. The importance of the research lies in giving particular importance to the development of the auditor’s tasks in following up the environmental audit and follow-up of the environmental reports issued by the competent supervisory committees to rationalize the calculation of the environmental cost in a correct and fair manner with the disclosure of deliberate or omissions errors in the environmental audit process. The auditor determines the weaknesses directly and thus contributes to the control body to establish direct points on waste operations as the environmental cost is a hidden cost under other cost items.